Hygiene in relation to the home - Stingley, Sadie (My University, 1896)
Introduction: Of all the influences which determine the life of the individual and on which his weal and woe depends, undoubtedly the nature of his food is one of the weightiest. Everyone knows how not only our strength and muscles, but also the whole mental tone depends upon the nature of the food.
Citation: Stingley, Sadie. Hygiene in relation to the home. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Life; Strength; Muscle; Mental tone; Theses; Manuscripts (documents)